2022
DOI: 10.1111/bjh.18312
|View full text |Cite
|
Sign up to set email alerts
|

Impaired humoral and cellular response to primary COVID‐19 vaccination in patients less than 2 years after allogeneic bone marrow transplant

Abstract: Summary Allogeneic haematopoietic stem cell transplant (HSCT) recipients remain at high risk of adverse outcomes from coronavirus disease 2019 (COVID‐19) and emerging variants. The optimal prophylactic vaccine strategy for this cohort is not defined. T cell‐mediated immunity is a critical component of graft‐versus‐tumour effect and in determining vaccine immunogenicity. Using validated anti‐spike (S) immunoglobulin G (IgG) and S‐specific interferon‐gamma enzyme‐linked immunospot (IFNγ‐ELIspot) assays we analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Using an ELISPOT-IFNγ quantification of in vitro expanded T cells, our detection rate of S1- and S2- specific T cells (50% and 61% of HSCT recipients and 60% and 100% of HC, respectively) was higher than in the study of Ram et al, (6) and of Lindemann et al (7) which referred positive response in 18% and 27% of HSCT recipients, respectively. On the other hand, in other studies [9] , [10] , [11] , the detection rates of specific T- cell response in patient groups were higher (70, 78, 82%). The highest detection rate was achieved using the S1-specific T-cell derived IFNγ-release assay in whole blood where positive T cell response was detected in 90.4% of HC and 72% of HSCT recipients.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Using an ELISPOT-IFNγ quantification of in vitro expanded T cells, our detection rate of S1- and S2- specific T cells (50% and 61% of HSCT recipients and 60% and 100% of HC, respectively) was higher than in the study of Ram et al, (6) and of Lindemann et al (7) which referred positive response in 18% and 27% of HSCT recipients, respectively. On the other hand, in other studies [9] , [10] , [11] , the detection rates of specific T- cell response in patient groups were higher (70, 78, 82%). The highest detection rate was achieved using the S1-specific T-cell derived IFNγ-release assay in whole blood where positive T cell response was detected in 90.4% of HC and 72% of HSCT recipients.…”
Section: Discussionmentioning
confidence: 62%
“…In some of the previous studies, the effects of gender [6] , [7] and type of vaccine [9] were observed in connection with antibody response but not with T cell responses. In concordance with their results, we did not find a significant association between the vaccine- specific T- cell response and age, gender, basal diagnosis or HSCT characteristics.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…dose, associated with a larger pool of persistent memory T cells (103,104,106). Inferior results in allo-HSCT recipients as compared with a healthy control group could be explained, at least in part, by a more immature immune system with more frequent lymphopenia and the use of immunosuppressants or steroids, the same predictive factors as those reported in humoral response studies.…”
Section: Cellular Responsementioning
confidence: 80%
“…Responses to COVID-19 vaccines are likely to be blunted in HCT or cell therapy recipients, compared with healthy individuals 6 . However, despite the scarcity of data, the high level of protection afforded to those vaccinated in the clinical trials, and the overall safety of the vaccine in clinical trials and post-emergency use authorization (EUA) experience, ASTCT and ASH strongly support vaccination of this vulnerable patient population, along with their caregivers, family members, and household contacts.…”
Section: Covid-19 Preventionmentioning
confidence: 99%